+0  
 
+3
134
1
avatar+73 

1(4x^2+7x+9)-(2x^2+10x+4)

 Sep 7, 2018
 #1
avatar
+1

Simplify the following:
(4 x^2 + 7 x + 9) - (2 x^2 + 10 x + 4)

 

Factor 2 out of 2 x^2 + 10 x + 4:
4 x^2 + 7 x + 9 - 2 (x^2 + 5 x + 2)

-2 (x^2 + 5 x + 2) = -2 x^2 - 10 x - 4:
-2 x^2 - 10 x - 4 + 4 x^2 + 7 x + 9

 

Grouping like terms, 4 x^2 - 2 x^2 + 7 x - 10 x - 4 + 9 = (4 x^2 - 2 x^2) + (7 x - 10 x) + (9 - 4):
(4 x^2 - 2 x^2) + (7 x - 10 x) + (9 - 4)

4 x^2 - 2 x^2 = 2 x^2:
2 x^2 + (7 x - 10 x) + (9 - 4)

7 x - 10 x = -3 x:
2 x^2 + -3 x + (9 - 4)

9 - 4 = 5:
=2x^2 - 3x + 5

 Sep 7, 2018

24 Online Users

avatar
avatar
avatar
avatar
avatar